PENGARUH PRODUK, SUMBER DAYA MANUSIA, LOKASI DAN BUKTI FISIK TERHADAP CITRA INSTITUSI DAN IMPLIKASINYA PADA KEPUTUSAN SISWA DALAM MEMILIH PERGURUAN TINGGI SWASTA DI PURWAKARTA - Fachmi Imannur Anwar; Djuni Akbar; Agus Supriyadi; Agus Buntoro (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze students' decisions in choosing private universities in Purwakarta, especially at the High School of Economics and Business Perdana Mandiri Purwakarta. Product, People, Place and Physical Evidance belonging to the High School of Economics and Business of Perdana Mandiri Purwakarta become Exogenous variable of research while Corporate image and Purchasing Decision serve as Endogen variable. In this research the sampling method used is non-probabilistic sampling. From the population of 11,770 high school / equivalent students consisting of 46 SMA and 23 SMK in purwakarta district. In this study the authors used a structural equation model (SEM). The result of the research shows that there is a significant correlation between exogenous variables and endogenous variables either partially or simultaneously, partially. The effect of P1 on BI through P2, P3, and P4 is 14.5%. The effect of P2 on BI through P1, P3, and P4 is 35.0%. The influence of P3 on BI through P1, P2, and P4 is 11.9%. The effect of P4 on BI through P1, P2, and P3 is 25.1%, while simultaneously the effect of exogenous variables on Endogenous variables (Institutional Image) with total influence of 86.5%. Partially, the relationship between exogenous variables and endogenous variables (purchase decision). The effect of P1 on KP through BI is 12.4%. The effect of P2 on KP through BI is 25.4%. The effect of P3 on KP through BI is 12.4 %, Effect of P4 to KP through BI is 19.2%, while simultaneous influence on Endogen variable (Purchase Decision) of 69,4%.